Genome-wide identification and expression analysis of new cytokinin metabolic genes in bread wheat (Triticum aestivum L.) - Muhammad Shoaib; Wenlong Yang; Qiangqiang Shan; Muhammad Sajjad; Aimin Zhang (PeerJ, 2019)
Cytokinins (CKs) are involved in determining the final grain yield in wheat. Multiple gene families are responsible for the controlled production of CKs in plants, including isopentenyl transferases for de novo synthesis, zeatin O-glucosyltransferases for reversible inactivation, β-glucosidases for reactivation, and CK oxidases/dehydrogenases for permanent degradation. Identifying and characterizing the genes of these families is an important step in furthering our understanding of CK metabolism. Using bioinformatics tools, we identified four new TaIPT, four new TaZOG, and 25 new TaGLU genes in common wheat. All of the genes harbored the characteristic conserved domains of their respective gene families. We renamed TaCKX genes on the basis of their true orthologs in rice and maize to remove inconsistencies in the nomenclature. Phylogenetic analysis revealed the early divergence of monocots from dicots, and the gene duplication event after speciation was obvious. Abscisic acid-, auxin-, salicylic acid-, sulfur-, drought- and light-responsive cis-regulatory elements were common to most of the genes under investigation. Expression profiling of CK metabolic gene families was carried out at the seedlings stage in AA genome donor of common wheat. Exogenous application of phytohormones (6-benzylaminopurine, salicylic acid, indole-3-acetic acid, gibberellic acid, and abscisic acid) for 3 h significantly upregulated the transcript levels of all four gene families, suggesting that plants tend to maintain CK stability. A 6-benzylaminopurine-specific maximum fold-change was observed for TuCKX1 and TuCKX3 in root and shoot tissues, respectively; however, the highest expression level was observed in the TuGLU gene family, indicating that the reactivation of the dormant CK isoform is the quickest way to counter external stress. The identification of new CK metabolic genes provides the foundation for their in-depth functional characterization and for elucidating their association with grain yield.